Analysis Of Lard In Palm Oil Using Long‑wave Near‑infrared (lw‑nir) Spectroscopy And Gas Chromatography‑mass Spectroscopy (gc–ms) - Mutia Nurulhusna Hussain; Katrul Nadia Basri; Syariena Arshad; Shuhaimi Mustafa; Jamilah Bakar; Mohd Fared Abdul Khir (Springer Nature, 2024)
Indexed by SCOPUS/ERA